Coping with Negative Work Experience and Work-related Family Issues: Spirituality as A Buffer against Emotional Exhaustion and (Asian Business Research, 2016)
The current research examined the effects of psychological contract breach on employees’ work to family conflict and their partners’ family-work conflict. This study also investigated the buffering effect of employee spirituality on the employees’ emotional exhaustion caused by such conflicts. Analysis of a sample of 235 employee-partner dyads (188 men, 47 women, M age = 44 yr.) from a plastics corporation in Taiwan found as positive relationship between psychological contract breach and family issues, through employee’s emotional exhaustion. Employees with high spirituality were discovered to weaken the relationships between psychological contract breach and employees’ emotional exhaustion and both family issues. This study highlighted the value of psychological contract breach on family issues from work to family in further research.